Casts of an Island 2024 - Pericleous, Vicky (My University, 2024)
This exhibition marks a pivotal transformation of an old industrial building on the Limassol waterfront into a public space. The exhibition highlights a tumultuous historical era for Cyprus during the last 50 years and commemorates the tragedy of 1974 when the Turkish invasion was followed by the division of the island. This period was marked by numerous efforts toward healing and societal restructuring amidst significant global upheavals. The artistic expressions evoked by Nicos Chr. Pattichis covers a broad spectrum of proposals that range from varied painting techniques, constructions, installations, and videos, all representing facets of creative endeavour relating to the unity of universal culture. The artworks featured are curious accumulations of diverse materials, transformations of archival substances and everyday objects with reimagined aesthetic roles, along with new mappings between fictive urban planning and psychogeography. This creative polyphony naturally leads to deep reflections on critical issues tied to historical memory and social progress across all sectors of ‘real’ life, fostering the development of new thinking aimed at building a redemptive worldview. Many of the works are part of the non-profit organisation CYCO (Cyprus Contemporary Art Center).
Studies for a Place, The House of Leda, 2023 (video duration: 11’:46’’), video
The Tail of the Image, 2020, Vicky Pericleous, (video duration:08’:13’’)
Keywords: Arts; Exhibitions; Casts of an Island; Historical memory; National imagination of Cyprus; Art collection; Political constructs; Sociopolitical imaginaries; Cultural Landscapes; Mnemonics of space